Up and down the spectrum: upconversion nanocrystal and semiconductor material fused into a single nanocomposite - Gorris, Hans H; Farka, Zdeněk (Light, science & applications, 2022)
A nanocomposite consisting of a cubic EuSe semiconductor material grown on a hexagonal upconversion nanoparticle has overcome the crystal lattice mismatch that typically prevents the epitaxial growth of such heterogeneous nanocrystals. Eu3+ at the interface layer shows its characteristic red emission band both under UV excitation light due to energy transfer from the semiconductor and under NIR excitation light due to energy transfer after photon-upconversion. Data storage and security applications are suggested for this new nanocomposite.